Perceived Teacher Autonomy Support and School Engagement of Tibetan Students in Elementary and Middle Schools: Mediating Effect of Self-Efficacy and Academic Emotions - Li, Wei; Gao, Wenyang; Sha, Jingrong (Frontiers in Psychology, 2020)
School engagement (SE) refers to the intensity and quality of emotions involved when students commence and carry out learning activities, and it includes behavioral, emotional, and cognitive engagements. A high SE level promotes academic achievement, reduces students’ behavioral problems, and prevents them from dropping out of school. This study, whose participants were 819 students from the Tibetan areas, explored the impact of teacher autonomy support (TAS) on their SE and its mechanism behind. The results showed that TAS had a positive impact on SE, while the students’ self-efficacy had a mediating effect between TAS and SE. On the one hand, TAS affected self-efficacy through academic interest and ultimately influenced SE; on the other hand, TAS negatively affected academic anxiety, which indirectly inhibited academic anxiety’s impact on SE through self-efficacy. The theoretical and practical implications of the research results were also discussed.